Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
041-0030-001 wmc/wjb/ac/616 International 14th April, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, RAY COX MEMORIAL. With reference to your telephone message, we have consulted with our Dr. Morgan, and he agrees that the best plan would be for you, as proposed, to purchase the apparatus approved by the Belgian surgeons. We therefore enclose a cheque for £40 towards the cost. The original sum promised to us was between £55 and £60 for this purpose. The Southampton Joint Council, which is collecting the money, desires that some plate should be affixed to the apparatus, worded thus: "The Ray Cox (Southampton) Memorial Apparatus". Can you manage this? As soon as you let us know the exact balance due in payment of the purchase we will transmit a further cheque. Yours faithfully, General Secretary. Cheque. 292/946/41/30